Data and Code for "A primitive-based representation of dance: Modulations by experience and perceptual validity" - Leh, Amalaswintha; Justus Liebig University Giessen (My University, 2023)
Motion capture data (.BVH and .C3D) and code for "A primitive-based representation of dance: Modulations by experience and perceptual validity". Code includes the Temporal movement primitive model (requires PyTorch; https://pytorch.org) and code for a Bayesian ANCOVA (requires PyMC; https://www.pymc.io).
Keywords: Movement Primitives; Dance; Motion Capture; Motor Experience; ddc:150; ddc:792; ddc:796